Bentuk Cyberbullying Terhadap Publik Figur Di Media Sosial Instagram (Studi Kasus Pada “Rahmawati Kekeyi”) - Novarizal, Riky; Dhea Pasela, Anjeli (UIR PRESS, 2021)
Even though the Indonesian state has Law No.11 of 2009 concerning Electronic Information and Transactions in Article 27 paragraph (3) of the ITE Law which regulates criminal sanctions for perpetrators of bullying insults, this does not necessarily stop bullies from intensifying their actions in the media social. An Indonesian public figure named Kekeyi is hotly discussed on Instagram. Not everything done by Kekeyi received positive responses. Kekeyi is one of the many public figures in Indonesia who experience cyberbullying on social media. Research aims to determine the forms of cyberbullying that Kekeyi accepted on his Instagram account because cyberbullying has various forms. This study uses a visual criminology method with content analysis. The theoretical basis used is critical victimology theory. Based on the visuals and data analysis conducted, it is concluded that all forms of cyberbullying by Price & Dalgleish (2010) have been experienced by the public figure of Rahmawati Kekeyi on Instagram social media. Which consists of called names (giving negative names), image of victim spread, threats to physical safety (threatened physical harm), and opinion slammed (derogatory opinion). In the context of cyberbullying, it was found that cyberbully in the form of opinion slammed is a form of cyberbullying that is mostly experienced by Kekeyi. And most occur in the comments column.